Advances in Meniscal Tissue Engineering - Umile Giuseppe Longo; Mattia Loppini; Francisco Forriol; Giovanni Romeo; Nicola Maffulli; Vincenzo Denaro (Stem Cells International)
Meniscal tears are the most common knee injuries and have a poor ability of healing. In the last few decades, several techniques have been increasingly used to optimize meniscal healing. Current research efforts of tissue engineering try to combine cell-based therapy, growth factors, gene therapy, and reabsorbable scaffolds to promote healing of meniscal defects. Preliminary studies did not allow to draw definitive conclusions on the use of these techniques for routine management of meniscal lesions. We performed a review of the available literature on current techniques of tissue engineering for the management of meniscal tears.